Intertemporal Commodity Futures Hedging and the Production Decision - HO, THOMAS S. Y. (Journal of Finance, 1984)
ABSTRACT This paper deals with the producer's optimal use of commodity futures in hedging. The framework for analysis is an intertemporal consumption and investment model. The producer makes his production decisions at the beginning of the period and realizes his return at the end of the time interval. During the period, he faces both price and output uncertainties. In applying stochastic dynamic programming methods, this paper shows the effect of these risks on his consumption behavior. Further, the paper investigates his optimal hedging positions in the futures market over time and his optimal production decisions. Finally, implications of these results on the futures markets are discussed.